Talent Management Strategy for Nottinghamshire Police - Thedchanamoorthy, Geetha (2011)
This consultancy project examines an effective way of providing a programme of Talent Management (TM) within Nottinghamshire Police. A programme of Talent Management is consistent with the organisation’s “Policing for You” vision to drive forward change, improve performance and deliver a better quality of service for the public. It aims to ensure that Nottinghamshire Police provides the correct services, in the correct manner, in the most cost-effective way possible for the public. The organisation is currently going through a re-structure as a result of budget cuts advocated by the government’s spending review (police funding cut by 4% a year). In the process of restructuring, an effective talent management programme is necessary in order to meet the tough financial challenges placed upon the organisation. It aims to become the best performing force in the UK by 2015.